Effect of joint pathology, surface preparation and fixation methods on union frequency after first metatarsophalangeal joint arthrodesis: A systematic review of the English literature. Issue 3 (September 2017) - Korim, Muhammad Tawfiq; Mahadevan, Devendra; Ghosh, Arijit; Mangwani, Jitendra
Highlights: A high union frequency can be expected following first MP joint arthrodesis. Higher union frequencies were observed with joint preparation methods using hand tools such as curettes and rongeurs compared to when power saws or ball and socket reamers were used. There were significantly more unions in MP joint arthrodesis where the primary diagnosis was hallux rigidus. The PROMS improve following surgery and infection and re-operation frequencies are low. Abstract: Background: The aim of this systematic review was to perform a qualitative synthesis of the current literature to determine the union frequencies for first metatarsophalangeal joint arthrodesis as well as the influence of pathology, joint preparation and fixation methods on union. Methods: MEDLINE and EMBASE were searched to identify relevant studies reporting on first metatarsophalangeal joint union frequencies. Results: 26 studies with 2059 feet met our inclusion criteria. The mean age was 60 years (range 18–84) and the mean follow-up was 32.6 months (range 1.5–156). The union frequency was 93.5% (1923/2059). The union frequencies were significantly higher when low velocity joint preparation methods were used ( P < 0.0001, Chi Square 22.5) and the pathology was hallux rigidus ( P = 0.002, Chi square 9.3). There were similarly high union frequencies with crossed screws, locking plate and non-locking plates. Conclusions: High union frequency can be expected following first metatarsophalangeal arthrodesis, especially when low velocity joint preparation methods are used in patients with hallux rigidus.